2011
DOI: 10.1080/09712119.2011.621537
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of natural and synthetic vitamin E on production performance, egg quality and vitamin E content of yolk in laying hens

Abstract: A total of two hundred 35-week-old (Hy-line brown) layers were randomly assigned to 4 treatments with 10 replications and 5 layers per replicate (1 layer per cage). Dietary treatments were: (1) CON (basal diet); (2) S150, CON ' synthetic vitamin E (VE) 150 IU/kg; (3) N50, CON ' natural VE 50 IU/kg; and (4) N75, CON ' natural VE 75 IU/kg. Dietary VE led to a greater Haugh unit (HU) and VE concentration in yolk (p B0.05) compared with CON group, whereas the egg production, feed intake, egg weight, eggshell stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Ehran and Bolukbasi (2011) found that dietary supplementation with 85 U vitamin E for laying hens increased Haugh units. Yan and Kim (2011) found that dietary supplemental vitamin E improved the Haugh units of laying hens compared with those of hens fed basal diet in 35week-old (Hy-line brown) layers. Rama Rao et al (2001) indicated that Haugh unit score and egg shell weight were not influenced by supplementary choline (760 and 1520 mg/kg) in diets of broiler breeders (29 to 48 weeks of age).…”
Section: (Table 3): Effects Of Dietary Single and Combined Addition Omentioning
confidence: 94%
“…Ehran and Bolukbasi (2011) found that dietary supplementation with 85 U vitamin E for laying hens increased Haugh units. Yan and Kim (2011) found that dietary supplemental vitamin E improved the Haugh units of laying hens compared with those of hens fed basal diet in 35week-old (Hy-line brown) layers. Rama Rao et al (2001) indicated that Haugh unit score and egg shell weight were not influenced by supplementary choline (760 and 1520 mg/kg) in diets of broiler breeders (29 to 48 weeks of age).…”
Section: (Table 3): Effects Of Dietary Single and Combined Addition Omentioning
confidence: 94%